2020
DOI: 10.5539/jas.v12n4p271
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Analysis of Five Egyptian Buffalo Populations Using Microsatellite Markers

Abstract: For assessing the genetic diversity and genetic characterization of five Egyptian buffalo populations a total of 12 microsatellite markers were used. The total number of buffaloes sampled was 80, collected at random from five farms in five different governorates; Cairo, Kafr El-Sheikh, Shebeen El-Kom, Menoufia, and Beni Suef. The genetic parameters (allelic diversity, allelic frequencies, observed heterozygosity, unbiased expected heterozygosity, and polymorphic information content) were calculated using three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…PIC value is a parameter indicative of the degree of in formativeness of a microsatellite, may range from 0 to 1. PIC values calculated in this study were comparable with those revealed by Popa et al [ 58 ] in the Romanian buffalo population (0.4335–0.632), Saputra et al [ 53 ] in the Indonesian swamp buffalo population (0.360–0.740), Merdan et al [ 64 ] in five Egyptian buffalo populations (0.65–0.92), Darestani et al [ 59 ] in Iranian indigenous buffalo populations (0.33–0.86), Uffo et al [ 36 ] in Cuban water buffalo populations (0.169–0.809), Marrero et al [ 56 ] in Cuban and Brazilian buffaloes (0.321–0.703), Unal et al [ 12 ] in Turkish water buffalo population (0.14–0.82), Acosta et al [ 57 ] in Cuban water buffalo population (0.201–0.777), Jaayid and Dragh [ 61 ] in Iraqi buffalo population (0.11–0.80) and by Ángel-Marín et al [ 10 ] in Colombian water buffalo herds (0.43–0.81). Moreover, results of many studies on Indian and Guilan buffalo breeds revealed also high values of PIC (0.52–0.88) for most studied markers [ 14 , 15 , 65 , 66 ].…”
Section: Discussionsupporting
confidence: 91%
“…PIC value is a parameter indicative of the degree of in formativeness of a microsatellite, may range from 0 to 1. PIC values calculated in this study were comparable with those revealed by Popa et al [ 58 ] in the Romanian buffalo population (0.4335–0.632), Saputra et al [ 53 ] in the Indonesian swamp buffalo population (0.360–0.740), Merdan et al [ 64 ] in five Egyptian buffalo populations (0.65–0.92), Darestani et al [ 59 ] in Iranian indigenous buffalo populations (0.33–0.86), Uffo et al [ 36 ] in Cuban water buffalo populations (0.169–0.809), Marrero et al [ 56 ] in Cuban and Brazilian buffaloes (0.321–0.703), Unal et al [ 12 ] in Turkish water buffalo population (0.14–0.82), Acosta et al [ 57 ] in Cuban water buffalo population (0.201–0.777), Jaayid and Dragh [ 61 ] in Iraqi buffalo population (0.11–0.80) and by Ángel-Marín et al [ 10 ] in Colombian water buffalo herds (0.43–0.81). Moreover, results of many studies on Indian and Guilan buffalo breeds revealed also high values of PIC (0.52–0.88) for most studied markers [ 14 , 15 , 65 , 66 ].…”
Section: Discussionsupporting
confidence: 91%
“…Highly variable SSR markers extracted in the present study could be utilized to find genetic diversity ( Barker et al, 1997 ; Zhang et al, 2020 ). The SSR markers from different breeds could be used to find polymorphic SSRs ( Moore et al, 1995 ) and their utilization in the study of genetic diversity of respective breeds ( Moioli et al, 2001 ; Merdan et al, 2019 ; Vohra et al, 2021 ; Ünal et al, 2021 ). We also extracted ∼270000 polymorphic SSRs in the Mediterranean buffalo breed with respect to Murrah, Bangladesh, Jaffrabadi, and Egyptian breeds.…”
Section: Resultsmentioning
confidence: 99%